Keefektivan Model Pembelajaran Discovery Learning dalam Meningkatkan Hasil Belajar Informatika Siswa Kelas X.3 SMA Negeri 14 Maros - Naldi Naldi; Dian Safitri; Sadriana Ayu; Nasir Nasir (Lembaga Pengembangan Kinerja Dosen, 2024)
The study aims to determine the effectiveness of the discovery learning learning model in improving informatics learning outcomes of grade X. 3 students of SMA Negeri 14. The Classroom Action Research Method (PTK) is implemented in two cycles. The subjects of the study consisted of 34 students of grade X.3. Collection techniques include documentation, observation, and tests. From the results of the study, it can be concluded that the Discovery Learning Model learning model is very effective when applied in the classroom.